Excellent Response to Nivolumab and Ipilimumab in Metastatic Gastroesophageal Junction Squamous Carcinoma. (11th July 2019) - Sadagopan, Narayanan; Devoe, Craig
Abstract : Unresectable gastroesophageal junction (GEJ) cancers have a poor prognosis and limited treatment options. We report the case of a patient with a Siewert class III gastroesophageal junction squamous carcinoma with metastatic spread into the liver who had an exceptional response to a combination therapy of nivolumab and ipilimumab despite being programmed death-ligand 1 (PD-L1) negative, microsatellite stable (MSS), and having a low tumor mutational burden. He initially experienced disease progression on the chemotherapy regimens modified DCF and FOLFIRI resulting in limited functional status, esophageal stent placement, and feeding tube placement. After about 6 months on nivolumab and ipilimumab, he had near-complete disease resolution. He was able to return to his baseline functional status, as well as have the esophageal stent and feeding tube removed. Our case contributes to the value of exploring immunotherapy as an option for a variety of hard to treat cancers.